A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
kayla1098
 one year ago
Given that f (x) = x^2 + 3x + 6 and g (x) = x  3 /2 solve for f (g (x)) when x = 1
kayla1098
 one year ago
Given that f (x) = x^2 + 3x + 6 and g (x) = x  3 /2 solve for f (g (x)) when x = 1

This Question is Open

ybarrap
 one year ago
Best ResponseYou've already chosen the best response.0First, set x=1 in g(x): $$ g(1)=1\cfrac{3}{2}=\cfrac{1}{2} $$ This now becomes the input to f(x), where here \(x=\cfrac{1}{2}\): $$ f(\cfrac{1}{2})=? $$ Does this make sense?
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.